Helioclim 3 and Meteonorm 6 short wave irradiance validation over Africa - Ineichen, Pierre (2010)
Downward short wave incoming irradiances play a key role in the radiation budget at the earth surface. The monitoring of this parameter is essential for the understanding of the basic mechanisms involved in climate change, such as the greenhouse effect, the global dimming, the change in cloud cover and precipitations, etc. The use of geostationary satellite observations becomes crucial, since they allow the retrieval of irradiance at the surface, with the best spatial and temporal coverage. This study presents a common validation of two radiation products (Helioclim 3 and Eumetsat Ocean and Sea Ice Facility) and one software product (Meteonorm 6) against ground data from 19 stations covering up to one year of measurements over Europe and Africa. The overall conclusion is that the products are comparable in terms of bias and standard deviation, with lower bias and standard deviation over Europe. The surface solar irradiance is retrieved over the African continent with an average standard deviation of 21% and a negligible bias. If the atmospheric aerosol load becomes a better known input parameter, it remains sparlsy acquired over the African continent. On the other hand, the present validation shows that the atmospheric water vapor, retrieved from ground temperature and relative humidity, has a non-negligible effect on the results and should be better evaluated.